To multiply 2/3 by 1 2/9, you need to convert the mixed number 1 2/9 to an improper fraction.
To convert 1 2/9 to an improper fraction, you can multiply the whole number 1 by the denominator 9 and add the numerator 2. Then, you put the sum over the denominator 9.
1 * 9 + 2 = 9 + 2 = 11
So, 1 2/9 as an improper fraction is 11/9.
Now, you can multiply 2/3 by 11/9:
(2/3) * (11/9)
To find the product of two fractions, you multiply the numerators together and multiply the denominators together.
So,
(2/3) * (11/9) = (2 * 11) / (3 * 9) = 22/27
Therefore, the answer is 22/27.
multiply 2/3 by 1 2/9 whats the right awnser
11 answers
multiply 7/10 by 1 1/4
To multiply 7/10 by 1 1/4, we need to convert the mixed number 1 1/4 to an improper fraction.
To convert 1 1/4 to an improper fraction, we multiply the whole number 1 by the denominator 4 and add the numerator 1, then put the sum over the denominator 4.
1 * 4 + 1 = 4 + 1 = 5
So, 1 1/4 as an improper fraction is 5/4.
Now, we can multiply 7/10 by 5/4:
(7/10) * (5/4) = (7 * 5) / (10 * 4) = 35/40
To simply the fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 5.
35/40 ÷ 5/5 = (35/5) / (40/5) = 7/8
Therefore, the answer is 7/8.
To convert 1 1/4 to an improper fraction, we multiply the whole number 1 by the denominator 4 and add the numerator 1, then put the sum over the denominator 4.
1 * 4 + 1 = 4 + 1 = 5
So, 1 1/4 as an improper fraction is 5/4.
Now, we can multiply 7/10 by 5/4:
(7/10) * (5/4) = (7 * 5) / (10 * 4) = 35/40
To simply the fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 5.
35/40 ÷ 5/5 = (35/5) / (40/5) = 7/8
Therefore, the answer is 7/8.
whats simplest form
The simplest form of 7/8 is already in its simplest form, and there are no common factors between the numerator 7 and the denominator 8 that can be further reduced. So, 7/8 is already in simplest form.
whats 7/8 by 3 1/2
To divide 7/8 by 3 1/2, we need to convert the mixed number 3 1/2 to an improper fraction.
To convert 3 1/2 to an improper fraction, we multiply the whole number 3 by the denominator 2 and add the numerator 1, then put the sum over the denominator 2.
3 * 2 + 1 = 6 + 1 = 7
So, 3 1/2 as an improper fraction is 7/2.
Now, we can divide 7/8 by 7/2:
(7/8) ÷ (7/2)
To divide two fractions, we multiply the first fraction by the reciprocal of the second fraction.
So,
(7/8) ÷ (7/2) = (7/8) * (2/7)
To simplify the multiplication, we can cancel out common factors between the numerators and denominators if they exist. In this case, the factors 7 can be canceled out.
(7/8) * (2/7) = (1/8) * (2/1) = 2/8
To simplify the fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 2.
2/8 ÷ 2/2 = (2/2) / (8/2) = 1/4
Therefore, the answer is 1/4.
To convert 3 1/2 to an improper fraction, we multiply the whole number 3 by the denominator 2 and add the numerator 1, then put the sum over the denominator 2.
3 * 2 + 1 = 6 + 1 = 7
So, 3 1/2 as an improper fraction is 7/2.
Now, we can divide 7/8 by 7/2:
(7/8) ÷ (7/2)
To divide two fractions, we multiply the first fraction by the reciprocal of the second fraction.
So,
(7/8) ÷ (7/2) = (7/8) * (2/7)
To simplify the multiplication, we can cancel out common factors between the numerators and denominators if they exist. In this case, the factors 7 can be canceled out.
(7/8) * (2/7) = (1/8) * (2/1) = 2/8
To simplify the fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 2.
2/8 ÷ 2/2 = (2/2) / (8/2) = 1/4
Therefore, the answer is 1/4.
multiply 7/8 by 3 1/2 convert the product to be a mixed number
To multiply 7/8 by 3 1/2, we need to convert the mixed number 3 1/2 to an improper fraction.
To convert 3 1/2 to an improper fraction, we multiply the whole number 3 by the denominator 2 and add the numerator 1, then put the sum over the denominator 2.
3 * 2 + 1 = 6 + 1 = 7
So, 3 1/2 as an improper fraction is 7/2.
Now, let's multiply 7/8 by 7/2:
(7/8) * (7/2) = (7 * 7) / (8 * 2) = 49/16
To convert 49/16 to a mixed number, we divide the numerator 49 by the denominator 16.
49 ÷ 16 = 3 remainder 1
The whole number is the quotient (3), the remainder is the numerator of the fractional part (1), and the denominator remains the same.
Therefore, the product of 7/8 and 3 1/2 is 3 1/16.
To convert 3 1/2 to an improper fraction, we multiply the whole number 3 by the denominator 2 and add the numerator 1, then put the sum over the denominator 2.
3 * 2 + 1 = 6 + 1 = 7
So, 3 1/2 as an improper fraction is 7/2.
Now, let's multiply 7/8 by 7/2:
(7/8) * (7/2) = (7 * 7) / (8 * 2) = 49/16
To convert 49/16 to a mixed number, we divide the numerator 49 by the denominator 16.
49 ÷ 16 = 3 remainder 1
The whole number is the quotient (3), the remainder is the numerator of the fractional part (1), and the denominator remains the same.
Therefore, the product of 7/8 and 3 1/2 is 3 1/16.
multiply 1 2/3 by 6 1/2 convert it into a mixed number
To multiply 1 2/3 by 6 1/2, we first need to convert the mixed numbers to improper fractions.
To convert 1 2/3 to an improper fraction, we multiply the whole number 1 by the denominator 3 and add the numerator 2, then put the sum over the denominator 3.
1 * 3 + 2 = 3 + 2 = 5
So, 1 2/3 as an improper fraction is 5/3.
To convert 6 1/2 to an improper fraction, we multiply the whole number 6 by the denominator 2 and add the numerator 1, then put the sum over the denominator 2.
6 * 2 + 1 = 12 + 1 = 13
So, 6 1/2 as an improper fraction is 13/2.
Now, we can multiply 5/3 by 13/2:
(5/3) * (13/2)
To multiply fractions, we multiply the numerators together and multiply the denominators together.
5 * 13 = 65
3 * 2 = 6
So, (5/3) * (13/2) = 65/6.
To convert 65/6 to a mixed number, we divide the numerator 65 by the denominator 6.
65 ÷ 6 = 10 remainder 5
The whole number is the quotient (10), the remainder is the numerator of the fractional part (5), and the denominator remains the same.
Therefore, the product of 1 2/3 and 6 1/2 is 10 5/6.
To convert 1 2/3 to an improper fraction, we multiply the whole number 1 by the denominator 3 and add the numerator 2, then put the sum over the denominator 3.
1 * 3 + 2 = 3 + 2 = 5
So, 1 2/3 as an improper fraction is 5/3.
To convert 6 1/2 to an improper fraction, we multiply the whole number 6 by the denominator 2 and add the numerator 1, then put the sum over the denominator 2.
6 * 2 + 1 = 12 + 1 = 13
So, 6 1/2 as an improper fraction is 13/2.
Now, we can multiply 5/3 by 13/2:
(5/3) * (13/2)
To multiply fractions, we multiply the numerators together and multiply the denominators together.
5 * 13 = 65
3 * 2 = 6
So, (5/3) * (13/2) = 65/6.
To convert 65/6 to a mixed number, we divide the numerator 65 by the denominator 6.
65 ÷ 6 = 10 remainder 5
The whole number is the quotient (10), the remainder is the numerator of the fractional part (5), and the denominator remains the same.
Therefore, the product of 1 2/3 and 6 1/2 is 10 5/6.